Evaluation of the metaphorical image in architecture - Ali Haidar Al-jamel; Naam Behnam Minouna (Iraqi Journal of Architecture and Planning, 2009)
The metaphorical image represented in the architectural works was subjected toevaluation by different social sectors perceiving them in the society. Despite thediversity in the studies related to metaphorical image. In addition, the specialstandards forwarded for metaphorical image were dependent on selective formula asthey were conjugated with the cultural context to which the critic belongs giving suchinterpretations. These studies.could not formulate a theoretical framework comprisedcultural contexts. Its methodology concentrated ontheconstructionof atheoreticalframework, the isolation of the variables related its main aspects, the clarification ofits measurements and the performance of a selected field study which includes themain aspects of the evaluation process.This papers aims to determine and describe factors influencing evaluation of themetaphorical image in architecture according to certain architectural patterns tospecimen from Iraqi environment. The framework included aspects represented by themetaphorical process, perception and evaluation.Using a special methodology the research hypotheses were checked and the datawere processed using the computer software SPSS for statistical analysis.